Analisis Sedimentasi di Sungai Way Besai - Ofik Taufik Purwadi; Dyah Indriana Kusumaastuti; Astika Murni Lubis (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2016)
Way Besai River's catchment area is used as agricultural, tourism, and hydroelectrica power plant (PLTA) purposes. PLTA Way Besai was built for generating electrical power using the height of a waterfall from Way Besai River, however nowadays PLTA Way Besai is having a decrease of electrical power because of the now happening drought. The power decrease reached until 40 MW while it used to have 90 MW power supply causing only a rough 50 MW energy power left to be operated. The metode that is used in estimating the value of sediment discharge is by using the Universal Soil Loss Equation (USLE) method and Measured Sediment Analysis. From the analysis results, the overall value of sediment was attained by merging the value of suspended load and bed load which is 170528,443 m 3 /year. The value of seddiment that is attained from USLE methode is 105520,738 m 3 /year.